Resistências cruzadas em biótipos de alisma plantago-aquatica resistentes ao bensulfurão-metilo e suas consequências - Moreira, Ilidio (2009)
The repetitive use of bensulfuron-methyl in rice fields from Sorraia, Sado and Mondego river valleys had selected resistant (R) populations of Alisma plantago-aquatica in Portugal, identified as So306, So307, Sa88, Mo190; Mo260, respectively. The response of R-biotypes to bensulfuron-methyl at 26 days after seeding (DAS) and 42 DAS and the cross-resistance either to ALS- inhibitors or to herbicides with other mode of action, was investigated in dose-response experiments. The results confirmed bensulfuron-methyl resistance in four biotypes, but not in Mo190, which had been also treated with bentazon every year. Younger plants (6 linear phyllodium, BBCH 116) were more susceptible to bensulfuron-merthyl than were older plants (6 expanded phyllodium, BBCH 126). Rbiotypes presented cross-resistance to all ALSinhibitors studied except for imazethapyr and metsulfuron-methyl. Resistance indeces (RI= ED50R /ED50 S) ranged frome 3 to 313 for the three sulfonylurea herbicides. Herbicides with different mode of action including bentazon, MCPA, oxadiazon and propanil showed resistance indices of one, indicating that all herbicides tested had equal activity to both Rand S-biotypes. It was concluded that these herbicides could be effective for the control of resistant A. plantago-aquatica biotypes in rice paddy fields.